A first look at the fish species of the middle Malinau: taxonomy, ecology, vulnerability and importance - Rachmatika, I.; Nasi, Robert; Sheil, Douglas; Wan, M. (Center for International Forestry Research, 2005)
The Malinau watershed in Northeast Kalimantan is essential for local communities both as a source of food and as a means of transport. The two main rivers sampled in this study Seturan and Rian rivers belong to the Malinau watershed. Seturan water catchment has high fish diversity (containes 47 fish species, 32 genera, 13 families and 3 orders) where these fishes are important to local people as food items, for sale and other purpuses. Local knowledge is clearly underlined by the fact that virtually all species recorded are known and distinguished by local informants. Some species are vulnerable to local-use changes (mainly sedimentation). This paper contains an initial checklist of the fish in the area bordered by the Seturan and Rian rivers. This list is annotated with special reference to the habitat each species is found in, and an assessment of which species have importance in local communities - and for what reasons.